Hodnocení finanční situace podniku a návrhy na její zlepšení. - Šafaříková, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Diplomová práce hodnotí finanční situaci společnosti INTERHOTEL VORONĚŽ a.s. v období let 2001 – 2005 pomocí vybraných metod finanční analýzy. Zjišťuje problémy a navrhuje možná řešení, která povedenou ke zlepšení finanční situace podniku do budoucna.

This thesis deals with the financial situation of the company INTERHOTEL VORONĚŽ Inc. within the years 2001 and 2005 on the basis of selected methods of the financial analysis. It determines problems and proposes possible solutions which result in the improvement of the financial situation of the firm in the following years.
Evulation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: INTERHOTEL VORONĚŽ a.s.; finanční analýza; elementární metody; poměrové ukazatele; INTERHOTEL VORONĚŽ a.s.; financial analysis; elementary methods; ratio indicators